Psychological Predictors of Visual and Auditory P300 Brain-Computer Interface Performance - Hammer, Eva M.; Halder, Sebastian; Kleih, Sonja C.; Kübler, Andrea (Frontiers in Neuroscience, 2018)
Brain-Computer Interfaces (BCIs) provide communication channels independent from muscular control. In the current study we used two versions of the P300 BCI: one based on visual the other on auditory stimulation. Up to now, data on the impact of psychological variables on P300 BCI control are scarce. Hence, our goal was to identify new predictors with a comprehensive psychological test-battery. A total of N = 40 healthy BCI novices took part in a visual and an auditory BCI session. Psychological variables were measured with an electronic test-battery including clinical, personality and performance tests. The personality factor “emotional stability” was negatively correlated (Spearman´s rho = -.416; p < .01) and an output variable of the non-verbal learning test (NVLT), which can be interpreted as ability to learn, correlated positively (Spearman´s rho = .412; p < .01) with visual P300 BCI performance. In a linear regression analysis both independent variables explained 24% of the variance. “Emotional stability” was also negatively related to auditory P300-BCI performance (Spearman´s rho = -.377; p < .05), but failed significance in the regression analysis. Psychological parameters seem to play a moderate role in visual P300-BCI performance. “Emotional stability” was identified as a new predictor, indicating that BCI users who characterize themselves as calm and rational showed worse BCI performance. The positive relation of the ability to learn and BCI performance corroborates the notion that also for P300 based BCIs learning may constitute an important factor. Further studies are needed to consolidate or reject the presented predictors.